St. Vincent and the Grenadines : 2001 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for St. Vincent and the Grenadines. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that in recent years, economy of St. Vincent and the Grenadines has diversified from bananas into services, mainly tourism, telephone and Internet-based marketing, and offshore financial services. However, the rate of economic growth declined sharply to 2 percent in 2000. The external current account deficit is estimated to have doubled to about 16 1\2 percent of GDP in 2001 largely owing to a decline in banana export volumes, higher imports, and a slowdown in tourism receipts and remittances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet